Knowledge, Attitudes, and Practices of Filipino BSIT in Food Technology Students toward Food Hygiene and Sanitation - Adling, Nikka Mae J.; Malinao, Rudolph John L. (Future Science / FSH-PH Publications, 2022)
This study mainly aims to determine the knowledge, attitudes, and practices among Filipino college students on food hygiene and sanitation in the context of flexible blended learning during the time of the COVID-19 pandemic. Twenty college students major in Bachelor of Science in Industrial Technology (BSIT) in Food Technology are purposively selected as the main respondents of the study. This mixed-method study reveals that the students have excellent knowledge, attitudes, and practices towards cleaning and sanitization procedures, the use of appropriate clothing, and the proper storage of foods during their laboratory activities. The very positive findings of the study indicate that the students have a high level of knowledge, attitude, and practices regarding general sanitary measures.